It's all in the past: temporal-context effects modulate subjective evaluations of emotional visual stimuli, regardless of presentation sequence - Czekóová, Kristína; Shaw, Daniel J.; Janoušová, Eva; Urbánek, Tomáš (Frontiers in Psychology, 2015)
The aim of this study was to investigate if and how temporal context influences the affective response to emotional images. To do so, we examined whether the subjective evaluation of a target image is influenced by the valence of its preceding image, and/or its overall position in a sequence of images. Furthermore, we assessed if these potentially confounding contextual effects can be moderated by a common procedural control: randomized stimulus presentation. Four groups of participants evaluated the same set of 120 IAPS pictures presented in four different sequences. Our data reveal strong effects of both aspects of temporal context in all presentation sequences, modified only slightly in their nature and magnitude. Furthermore, this was true for both valence and arousal ratings. Subjective ratings of negative target images were influenced by temporal context most strongly across all sequences. We also observed important gender differences: females expressed greater sensitivity to temporal-context effects and design manipulations relative to males, especially for negative images. Our results have important implications for future emotion research that employs normative picture stimuli, and contributes to our understanding of context effects in general.